(untitled) (PROKLA. Journal of Critical Social Science, 2023)
The change in gender relations during East Germany’s transformation from 1989/90 onwards has been little examined in research so far. Public childcare, in turn, represents a constitutive area in society for the regulation of gender relations. Using the example of the Saxony, Germany, this article examines the transformation of East German childcare during the 1990s and shows to what extent it was characterised by a process of re-familialisation of early childhood care as well as the municipalisation of day-care centres. Both processes led to a rationalisation of the public provision of childcare which largely resulted in the breakdown of previous supply structures.